2007
DOI: 10.1124/jpet.107.119792
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Induced Acute Renal Failure Is Associated with an Increase in the Cytokines Interleukin (IL)-1β, IL-18, IL-6, and Neutrophil Infiltration in the Kidney

Abstract: We have demonstrated that caspase-1-deficient (caspase-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
278
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(302 citation statements)
references
References 30 publications
21
278
0
3
Order By: Relevance
“…However, the synergetic cooperation Cyclosporine with TGFβ signaling pathway in the modulation of renal paracellular permeability has been confirmed by Feldman and colleagues [65]. In another study, expression of TGFβ has been demonstrated to be enhanced in cisplatin-induced Acute Kidney Injury (AKI) [66]. In agreement with these studies, we propose that that Cisplatin, Lead acetate and Cyclosporine can induce nephrotoxicity, at least in part, by affecting TGFβ signaling pathway, particularly Smad4 expression.…”
Section: Discussionsupporting
confidence: 74%
“…However, the synergetic cooperation Cyclosporine with TGFβ signaling pathway in the modulation of renal paracellular permeability has been confirmed by Feldman and colleagues [65]. In another study, expression of TGFβ has been demonstrated to be enhanced in cisplatin-induced Acute Kidney Injury (AKI) [66]. In agreement with these studies, we propose that that Cisplatin, Lead acetate and Cyclosporine can induce nephrotoxicity, at least in part, by affecting TGFβ signaling pathway, particularly Smad4 expression.…”
Section: Discussionsupporting
confidence: 74%
“…In this model, a single injection of 30 mg/kg cisplatin induced AKI in C57BL/6 mice within 2-3 d (22,42,43). In our experiments, blood urea nitrogen was increased from the control level of 45 mg/mL to 194 mg/dL at d 3 of cisplatin treatment.…”
Section: Mir-34a Induction During Cisplatin Nephrotoxicity In Vivomentioning
confidence: 61%
“…In the in vivo model, 30 mg/kg cisplatin was used to induce kidney injury in C57/BL6 mice. This dose was also used by this and other laboratories in previous studies (22,42,43,45). It is noteworthy that cisplatin at 30 mg/kg induced apoptosis mainly in proximal and distal tubules in kidneys, and not in collecting tubules or glomeruli; some necrosis was induced and mainly localized in proximal tubules (42).…”
Section: Discussionmentioning
confidence: 99%
“…80 However, not all studies document a consistent blockade of intrarenal inflammation and tubular necrosis in postischemic or toxic AKI in models upon blockade of the IL-1 axis. [81][82][83] These findings may imply that IL-1 is not a universal mediator of AKI and its role is context-dependent. Models of acute glomerular injury pose new questions.…”
Section: Aki Modelsmentioning
confidence: 99%